STRATEGI MARKETING PEMERINTAH DAERAH DALAM MENINGKATKAN PARTISIPASI PUBLIK PADA LAYANAN PUBLIK DIGITAL - Made Sudiari; Made Dewi Wahyuni; Zainal Firdaus Wardhana (CV. Adiba Aisha Amira, 2026)
This study aims to analyze local government marketing strategies to increase public participation in digital public services, identify emerging forms of public participation, and examine factors that support and hinder the effectiveness of these strategies. This study used a descriptive qualitative approach, focusing on local governments that have implemented digital public services. Data were collected through in-depth interviews with local government officials and service users, observations of digital public service platforms, and a documentary study of local government digital policies and content. The results indicate that local governments have implemented digital public service marketing strategies through the use of social media, websites, and service applications. However, these strategies are still dominated by informative and one-way communication approaches. The level of public participation is moderate and tends to be passive, with a predominance of administrative services and minimal public involvement in providing feedback and digital collaboration. Supporting factors include the commitment of local leaders and the availability of technological infrastructure, while inhibiting factors include limited human resource capacity, low public digital literacy, and the lack of integration of marketing functions into local public service management. This study confirms that local government marketing strategies need to be developed in a more participatory and public value-oriented manner to improve the success of digital public services and public participation.